The Rise of Low-Cost Carriers in Thailand - Sheriff, Thomas (2008)
With the global diffusion of Low-cost carriers (LCCs) and their ensuing popularity throughout the world, this paper examines whether the rise of LCCs in the Kingdom of Thailand is a sustainable phenomenon. In order to answer this, the paper begins with a survey on the origins and development of the worldwide LCC revolution and its emergence in the kingdom of Thailand. Through the research methodology of semi-structured interviews, it then proceeds to examine specifically whether market conditions are ripe for new LCCs to enter the market and whether the rise of LCCs in Thailand is a sustainable phenomenon. The paper concludes that, although there is a potential market for further LCCs within Thailand, a number of wider national and international contextual factors are likely to affect the future emergence, growth, development and sustainability of LCCs within the Kingdom of Thailand.